IMPROVING STUDENTS’ ABILITY IN USING PRESENT PERFECT CONTINUOUS TENSE THROUGH CONTEXTUAL TEACHING AND LEARNING - Anden, Carollina Dara; Bunau, Eusabinus; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether students’ abilities in using present perfect continuous tense can be improved through contextual teaching and learning and to explain the implementation of contextual teaching and learning in teaching present perfect continuous tense sentences to tenth grade students of Social Science at Sekolah Kristen AbdiWacana Pontianak. This research is based on a preliminary study which shows that the students still have lack of understanding of grammar patterns, especially in present perfect continuous tense sentences.This study implemented Classroom Action Research applied to address students’ problem in understanding and using present perfect continuous tense sentences. This study follows the basic pattern of Kurt Lewin and it is carried out in two cycles. The subjects in this study were students of class X IPS in SMA Kristen AbdiWacana Pontianak. The techniques used in collecting data were observation notes, interviews, questionnaires and tests. The result of this study indicates that the implementation of contextual teaching and learning was declared successful according to the achievement of criteria of success. The first criterion is that majority of students can reach a score ≥70, the second criterion is that the students were more active in learning activities. Key Words: Classroom Action Research, Contextual Teaching and Learning, Present Perfect Continuous Tense